2021
DOI: 10.1097/gox.0000000000003658
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Saudi Plastic Surgery Residents and Attendings of Online Education during the COVID-19 Pandemic

Abstract: Background: The world has faced an unprecedented challenge in controlling the spread of COVID-19—a rapid reshaping of the healthcare system and education was inevitable. Consequently, residency programs adopted e-learning as a social distancing tool for the continuity of the learning process. In this study, we explore the opinions and perspectives of plastic surgery attending doctors and residents on the implications of e-learning. Methods: After obtaining ethical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…7 It is believed that the current investigation adds considerable value to the current literature in Saudi Arabia with the largest sample size among Saudi plastic surgeons when compared to previously published articles on a similar targeted population. [11][12][13] There is a need for further research to identify all of the factors that influence the use of social media and to identify any demographic tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is believed that the current investigation adds considerable value to the current literature in Saudi Arabia with the largest sample size among Saudi plastic surgeons when compared to previously published articles on a similar targeted population. [11][12][13] There is a need for further research to identify all of the factors that influence the use of social media and to identify any demographic tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Several applications are mentioned in the literature, such as postoperative follow-up, wound management, flap monitoring, avoiding unnecessary clinic visits, cutting down on costs, quicker response time to referral requests, improved triage decisions, surgical education, and access to specialist care in remote areas. [4][5][6][7][8][9] COVID-19 markedly catalyzed the integration of telemedicine into plastic surgery practice. Salehi et al (2020) reported increased use of telemedicine among facial plastic surgeons in the United States in the aftermath of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, residency surgical training has become more challenging with increased working hours, increasing subspecializations, and centralizing surgical services [1]. The coronavirus disease-19 (COVID- 19) pandemic has further complicated practical surgical training due to these factors [2]. As a result, simulation and model-based surgical training have become increasingly popular [3].…”
Section: Introductionmentioning
confidence: 99%